Neonatal septic shock, a focus on first line interventions - Spaggiari, Valentina; Passini, Erica; Crestani, Sara; Roversi, Maria Federica; Bedetti, Luca; Rossi, Katia; Lucaccioni, Laura; Baraldi, Cecilia; Della Casa Muttini, Elisa; Lugli, Licia; Iughetti, Lorenzo; Berardi, Alberto (Acta Biomedica Atenei Parmensis, 2022)
Septic shock is a main cause of morbidity and mortality in neonates. Septic shock evolves from compensated to uncompensated through 3 distinct phases. Prompt diagnosis is challenging, since neonatal septic shock may overlap with the physiological changes occurring at birth. The outcome of septic shock depends on a prompt recognition of symptoms and a strict adherence to cardiopulmonary resuscitation guidelines. Fluid administration plays a major role in the initial management of septic shock. If there is no response to volume filling, inotropes must be infused within one hour of onset (dopamine, dobutamine, adrenaline). Life-threatening infections require immediate and aggressive empiric use of antimicrobials. In the pediatric age, delay in antibiotic initiation for treating septic shock is associated with poor outcome and increased risk of mortality. There is a gap regarding first line interventions in neonatal septic shock. This review addresses initial interventions in the treatment of neonatal septic shock and discusses currently available evidences., These interventions may allow to improve the outcome if they are promptly carried out.